Hijrat and Statelessness: Reimagining Agamben’s ‘Bare Life’ through Islamic Migration Theology in Contemporary Asia - Jamil Akhtar (International Journal of Social Service and Research, 2026)
This paper critically analyzes forced migration and statelessness in modern Asia within the theoretical framework of Giorgio Agamben’s bare life and Islamic theological concept of migration. It explores hijrat as a fundamentally and morally negotiated response to persecution, hence separating it from the exclusion. The comparative case studies of Asian refugees suggest that moral aspects, dignity, and communal solidarity contribute to enhancing agency, resilience, and dignity. Incorporating Agamben’s theory into Islamicate ethics, the paper presents a more sophisticated approach to the concepts of statelessness, citizenship, and resistance, thereby outlining the intersection of law, theology, and experience.